Heat capacity and thermal conductivity of multiferroics Bi1-xPrxFeO3 - Kallaev, S. N.; Omarov, Zairbek M.; Mitarov, R. G.; Sadykov, S. A.; Khasbulatov, Sidek V.; Reznichenko, Larisa A.; Bormanis, Karlis Ya; Kundzinsh, Maris (Taylor and Francis Ltd., 2019)
The heat capacity and thermal conductivity of multiferroics Bi1–xPrxFeO3 (0 ≤ x ≤ 0.50) has been studied in the temperature range of 130–800 K. A slight substitution of praseodymium for bismuth is found to lead to a noticeable shift of the antiferromagnetic phase transition temperature whilst the heat capacity increases. The temperature dependences of the heat capacity and thermal conductivity exhibit additional anomalies during phase transitions. The experimental results suggest that the excess heat capacity can be attributed to the Schottky effect for three-level states. The basic mechanisms of the heat transfer of phonons are highlighted and the dependence of the mean free path on temperature is determined.
Keywords: Research Subject Categories::NATURAL SCIENCES:Physics; heat capacity; Multiferroics; thermal conductivity